Unacceptable Antibiotic Resistance Rates for Helicobacter pylori in Turkey: Something Must Change - Gökçekuyu, Bilge Müge; Yılmaz, Özlem; Soytürk, Müjde; Ellidokuz, Hülya; Akpınar, Hale; Şimşek, İlkay (Turkish Journal of Gastroenterology, 2021)
Background: It is known that clarithromycin resistance has increased over the years (success rate 60%). The aim of the study was toinvestigate the importance of regional antimicrobial resistance rates for full accuracy of both diagnosis and treatment of Helicobacterpylori infection.Methods: This study was carried out in the University Hospital Department of Gastroenterology. A total of 116 patients were evaluatedwith upper gastrointestinal endoscopy. Gastric antrum and corpus biopsy samples were taken for the rapid urease test (RUT), culture,and antimicrobial susceptibility testing for the presence of H. pylori. Antimicrobial susceptibilities of isolated H. pylori strains for clarithromycinand levofloxacin were determined by the epsilometer test (E-test). Minimal inhibitory concentration values for clarithromycinand levofloxacin were ≥1 and >1 μg/mL, respectively.Results: H. pylori infection was considered clinically positive in 93 (80.2%) patients with either the RUT, culture, or histopathologicalexamination. Seventy (60.3%) of the patients had RUT positivity. Sixty (85.7%) of these 70 patients had RUT positivity within the first20 min. Among the 90 patients, who had a histopathological examination, HLO was positive in 76 (84.4%) patients. Fifty-two (44.8%)out of 116 patients were culture positive. Resistance rates for both clarithromycin and levofloxacin were high. In these 52 culture-positivepatients, resistance rates determined for clarithromycin and levofloxacin were 26.9% and 25.5%, respectively.Conclusion: Clarithromycin or levofloxacin-based treatment regimen may not be an ideal alternative therapy for Turkish patientsregardless of culture.